2008 IEEE Computer Society Conference on Computer Vision and Pattern Recognition Workshops 2008
DOI: 10.1109/cvprw.2008.4562971
|View full text |Cite
|
Sign up to set email alerts
|

Regularizing optical-flow computation using tensor theory and complex analysis

Abstract: This paper reports a technique that improves the robustness and accuracy in computing dense

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…For example, in Ref. 26, a regularization scheme is derived that is the most general regularization not penalizing rigid body motion, making it a natural regularization scheme for flows that are combinations of pure rotations, translations, etc. Mathematically, it means that the computation of the flow takes place in a highly restricted space of affine mappings, but it is more important to analyze the properties of such functions than it is to define and analyze the space rigorously.…”
Section: A Regularization Of the Potential Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in Ref. 26, a regularization scheme is derived that is the most general regularization not penalizing rigid body motion, making it a natural regularization scheme for flows that are combinations of pure rotations, translations, etc. Mathematically, it means that the computation of the flow takes place in a highly restricted space of affine mappings, but it is more important to analyze the properties of such functions than it is to define and analyze the space rigorously.…”
Section: A Regularization Of the Potential Functionmentioning
confidence: 99%
“…The regularization R 4 comes from the "engineering strain tensor" formulation of optical flow, a full description and explanation of which can be found in Ref. 26. Finally, R 5 is the potential and stream function form of the first-order "divcurl" regularization proposed by Suter.…”
Section: A Regularization Of the Potential Functionmentioning
confidence: 99%
“…The main drawback of these approaches is the smoothing of the optical flow field at motion and object boundaries. Koppel et al [9] have shown, that the regularization terms are only valid for 2d translatory motion and penalize valid changes in the motion field. Matching based approaches can handle arbitrary large motion vectors as long as the image distortion due to perspective effects is small.…”
Section: Introductionmentioning
confidence: 99%